Acoustic behaviour of 3D printed bio-degradable micro-perforated panels with varying perforation cross-sections. (March 2021) - Sailesh, R.; Yuvaraj, L.; Pitchaimani, Jeyaraj; Doddamani, Mrityunjay; Mailan Chinnapandi, Lenin Babu
Highlights: Bio-degradable micro-perforated panels with different perforation cross sections are prepared using 3D printing. Geometrical variations of perforations influence sound absorption coefficient of micro perforated panels significantly. The Divergent-Convergent perforation registered better performance compared to the conventional one in terms of peak absorption coefficient and bandwidth. The bandwidths covered by all other perforations for a given range of absorption coefficient were higher than the conventional perforation. Sound transmission losses are higher where the entry point of perforation is smaller in size. Abstract: Influence of perforations having arbitrarily varying cross-sections on the acoustic behaviour of 3D printed bio-degradable panels made of Poly Lactic Acid (PLA) is presented. Circular perforations having six different types of cross-sectional variations namely convergent-divergent (CD), divergent-convergent (DC), convergent (C), divergent (D) with two different perforation diameters are realized using Fused Filament Fabrication (FFF) based 3D printing. Sound absorption and transmission loss characteristics of these perforated panels are estimated through impedance tube technique. Results revealed that sound absorption of perforated panels with varying cross-section is better than uniform cross-sectional perforation for the given frequency range. Among, the different cross-sectional variations explored, comparable and lower transmission losses are exhibited by DC and D perforation pattern with respect to constant diameter 1 mm panel. The sound transmission results of all other five specimens were significantly higher than constant diameter 8 mm panel and observed to be increasing with frequency. Geometrical perforation variations are noted to be a very crucial factor in designing soundproof panels as presented in this work. The experimental results are compared with the numerical results and found to be in good agreement. Such numerical analysis paves the guidelines for designing optimum perforation geometries prior to the on-field testing of the functional prototypes.